A prospective study of injury patterns in high school pole vaulters - Rebella, G. S.; Edwards, J. O.; Greene, J. J.; Husen, M. T.; Brousseau, D. C. (The American Journal of Sports Medicine, 2008)
The pole vault is a track and field event that has witnessed a large increase in participants during the past 5 years. Currently there are no prospective studies that have evaluated injury patterns in pole vaulters.